2017
DOI: 10.1080/01677063.2017.1336236
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive disorder, which genes? Which functions? Which pathways? An integrated holistic view regarding OCD and its complex genetic etiology

Abstract: Obsessive-compulsive disorder (OCD) is characterized by recurrent obtrusive and repetitive acts typically occurred following anxiety. In the last two decades, studies done on the gene sequences, large-scale and point mutations and gene-gene, gene-environment and gene-drug interactions have led to the discovery of hundreds of genes associated with OCD. Although each gene in turn is a part of the etiology of this disorder; however, OCD, like other mental disorders is complex and a comprehensive and integrated vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Compulsions are neutral habits that have been linked to reduced fear and thereby strengthened. 30 (C) Neurobiological factors: Hyperactivity in frontalsubcortical thalamic pathways is implicated in the pathogenesis of OCD, according to data from imaging, pharmacological, and behavioral research (Figure 2). 31 Based on this hypothesis, hyperactivity in these pathways causes excessive activity in the frontal-subcortical networks, resulting in the behavioral dysfunction seen in OCD.…”
Section: Etiology Of Ocdmentioning
confidence: 99%
“…Compulsions are neutral habits that have been linked to reduced fear and thereby strengthened. 30 (C) Neurobiological factors: Hyperactivity in frontalsubcortical thalamic pathways is implicated in the pathogenesis of OCD, according to data from imaging, pharmacological, and behavioral research (Figure 2). 31 Based on this hypothesis, hyperactivity in these pathways causes excessive activity in the frontal-subcortical networks, resulting in the behavioral dysfunction seen in OCD.…”
Section: Etiology Of Ocdmentioning
confidence: 99%
“…TS, OCD, and ADHD are also highly heritable conditions [53][54][55][56][57][58] . Despite evidence for a substantial genetic contribution to disease risk, the identification and replication of genetic variants associated with these related conditions has been challenging.…”
Section: Genetic Riskmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) in OCD have found suggestive evidence for some single nucleotide polymorphisms (SNPs) and genes that are potentially involved in its pathogenesis (International Obsessive Compulsive Disorder Foundation Genetics, 2017 ). Yet, overall these findings remain rather inconclusive with no single genetic variant reliably replicating across individual studies (Sampaio et al, 2013 ; Bozorgmehr et al, 2017 ). These studies did, however, suggest that an increase in sample size will likely aid the identification of genome-wide significant loci, following the example of other psychiatric disorders like major depressive disorder (MDD) (Wray et al, 2018 ), attention-deficit hyperactivity-disorder (ADHD) (Demontis et al, 2019 ), or autism spectrum disorder (ASD) (Grove et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%